Electrical functionalization of thermoplastics by combining plasmadust coating and aerosol jet printing - Schramm, René; Hörber, Johannes; Dold, Christoph; Franke, Jörg (Advanced Materials Research, 2014)
Additive structuring and metallization technologies like Plasmadust or Aerosol Jet printing offer many advantages for future MID applications. Both digital writing technologies enable a highly flexible design of the circuit pattern and are capable of coating 3D substrates. Currently, Aerosol Jet printing is used to generate patterns with accurate and detailed features, and line widths of 100 μm. Plasmadust provides variable coating thicknesses up to 200 μm combined with a high process speed. Hence, a combination of both technologies appears to be advantageous for a broad range of MID applications. In this paper an initial study on the interconnection of plasmadust and Aerosol Jet generated conductive structures on thermoplastic substrate materials is presented. In this context different printing strategies and process variations are evaluated.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Additive metallization; Aerosol jet; Plasmadust; Structuring